New Trends in Islamic Political Parties in the Arab Spring Countries - Burdah, Ibnu (Al-Jamiah Research Centre, 2014)
The recent developments of Islamic political parties in the Arab spring countries show new orientation and agendas, i.e. reconfirmation of their commitment to democratic values, strengthening civil society, and adopting human rights principles. In the same time, they indicate not to be interested in the old Islamic agendas relating to jihad for Islamic states (dawlah IslÄmiyah) and âglobal Islamic governmentâ under one centralized caliphate (al-khilÄfah al-IslÄmiyyah). It is the case of Justice and Development Party (á¸¤izb al-âAdÄlah waâl-Tanmiyah) in Morocco, Freedom and Justice Party (á¸¤izb al-á¸¤urriyyah waâl-âAdÄlah) in Egypt, and Awakening Party (á¸¤izb al-Nahá¸ah) in Tunis. This paper seeks to explore and explain this new fact. Based on literary research and interviews with the leaders of the Justice and Development Party (á¸¤izb al-âAdÄlah waâl-Tanmiyah) in Morocco, the paper concludes that the new orientation and agendas of Islamic political parties in the Arab spring states are related to democratization in the world, strong waves of Arab spring in many Arab states, and the dynamics of the internal parties.[Perkembangan mutakhir partai-partai politik Islam di sejumlah negara Arab âMusim Semiâ menunjukkan adanya perubahan orientasi dan agenda baru, berupa penegasan kembali komitmen mereka terhadap nilai-nilai demokrasi, penguatan masyarakat sipil, dan adopsi prinsip-prinsip hak asasi manusia. Pada saat yang sama, mereka tampak kurang tertarik kepada agenda-agenda politik Islam lama seperti jihad bagi pendirian negara Islam dan pendirian pemerintahan Islam global di bawah satu khalifah yang tersentralisasi. Hal ini relevan terhadap kasus Partai Keadilan dan Pembangunan (á¸¤izb al-âAdÄlah waâl-Tanmiyah) di Maroko, Partai Kebebasan dan Keadilan (á¸¤izb al-á¸¤urriyyah waâl-âAdÄlah) di Mesir, dan Partai Kebangkitan (á¸¤izb al-Nahá¸ah) di Tunisia. Artikel ini berupaya mengeksplorasi dan menjelaskan fakta baru ini. Berdasarkan kajian pustaka dan wawancara dengan sejumlah petinggi Partai Keadilan dan Pembangunan di Maroko, penulis berkesimpulan bahwa orientasi baru ini terjadi akibat dari gelombang demokratisasi dunia, âangin kencang musim semiâ Arab yang begitu kuat, dan dinamika internal partai.]